2005
DOI: 10.1152/ajpregu.00735.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of membrane-associated carbonic anhydrase isoforms IV, IX, XII, and XIV in the rabbit: induction of CA IV and IX during maturation

Abstract: Several carbonic anhydrase (CA) isoforms are associated with plasma membranes. It is probable that these enzymes interact with anion transporters to facilitate the movement of HCO3− into or out of the cell. A better knowledge of CA isoform expression in a given tissue would facilitate a systematic examination of any associations with such transporters. We examined the expression of CAs IV, IX, XII, and XIV mRNAs in rabbit tissues, including kidney, heart, lung, skeletal muscle, liver, pancreas, gall bladder, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
2
23
0
2
Order By: Relevance
“…92 In contrast to mouse kidney, CAXIV is not abundantly expressed in human kidney 10 and CAXIV mRNA and protein are virtually undetectable in rabbit kidney cortex. 63 A complementary DNA sequence for a novel CA isoform, CAXV, was submitted to the NCBI in 2000 (GenBank s accession no. AF231122), and Hilvo et al 12 recently reported expression of CAXV mRNA in mouse tissues including kidney and brain.…”
Section: Caxiv and Caxvmentioning
confidence: 99%
See 2 more Smart Citations
“…92 In contrast to mouse kidney, CAXIV is not abundantly expressed in human kidney 10 and CAXIV mRNA and protein are virtually undetectable in rabbit kidney cortex. 63 A complementary DNA sequence for a novel CA isoform, CAXV, was submitted to the NCBI in 2000 (GenBank s accession no. AF231122), and Hilvo et al 12 recently reported expression of CAXV mRNA in mouse tissues including kidney and brain.…”
Section: Caxiv and Caxvmentioning
confidence: 99%
“…22,101 CAIX is abundantly expressed in the proximal gastrointestinal tract including the stomach and gall bladder but not in normal kidney. 63,102,103 CAIX expression is also observed in the basolateral membrane of enterocytes of duodenum and jejunum, with most abundant expression occurring in the crypts in regions where epithelial cells exhibit high proliferative capacity. 102 The function of CAIX in the gastric mucosa has yet to be defined, but basolateral expression of CAIX suggests a role in facilitation of chloride/ bicarbonate exchange resulting in bicarbonate extrusion across the basolateral membrane of gastric parietal cells coupled with proton secretion by gastric H þ , K þ ATPase.…”
Section: Caxii and Caixmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Of the 15 known mammalian CAs, six are extracellular: CA IV, VI, IX, XII, XIV, and XV (reviewed in ref. 24). CA IX, XII, and XIV are integral membrane proteins with an extracellular enzyme domain that is continuous with a single transmembrane domain.…”
mentioning
confidence: 99%
“…These results suggest that inhibition of luminal membrane-bound CA is important in preventing Cd-MT-induced damage. Among the many isoforms of CA, CA IV, XII, XIV, and XV are membrane-associated and reported to be located in the kidney, while CA XIV is not detected in the rabbit, but is detected in the mouse kidney [16, 17]. …”
Section: Discussionmentioning
confidence: 99%